The structure of lipid nanodisc-reconstituted TRPV3 reveals the gating mechanism - Shimada, Hiroto; Kusakizako, Tsukasa; Dung Nguyen, T H; Nishizawa, Tomohiro; Hino, Tomoya; Tominaga, Makoto; Nureki, Osamu (Nature structural & molecular biology, 2020)
Transient receptor potential vanilloid subfamily member 3 (TRPV3) is a temperature-sensitive cation channel. Previous cryo-EM analyses of TRPV3 in detergent micelles or amphipol proposed that the lower gate opens by α-to-π helical transitions of the nearby S6 helix. However, it remains unclear how physiological lipids are involved in the TRPV3 activation. Here we determined the apo state structure of mouse (Mus musculus) TRPV3 in a lipid nanodisc at 3.3 Å resolution. The structure revealed that lipids bound to the pore domain stabilize the selectivity filter in the narrow state, suggesting that the selectivity filter of TRPV3 affects cation permeation. When the lower gate is closed in nanodisc-reconstituted TRPV3, the S6 helix adopts the π-helical conformation without agonist- or heat-sensitization, potentially stabilized by putative intra-subunit hydrogen bonds and lipid binding. Our findings provide insights into the lipid-associated gating mechanism of TRPV3.